STUDY ON CATH HANDLING IN PURSE SEINE FISHERIES KM. BINTANG MAS AT PEKALONGAN FISHING PORT - Sari, Ratih Purnama; Larasati, Rakhma Fitria; Ikhsan, Suci Asrina; Akbar, R. Mohamad Adha; Habib, E.Y., M. (Politeknik Kelautan dan Perikanan Dumai, 2025)
Pekalongan National Fishing Port (PPN Pekalongan), a type B fishing port, is recognized for its well-managed facilities and serves as an operational base for purse seine vessels. Purse seines are widely employed to harvest schooling pelagic fish, most of which are species of high economic value, thus requiring appropriate handling to maintain quality. This study aims to examine the handling practices of purse seine catches on board KM. Bintang Mas Maritim, focusing on storage temperature, handling equipment, and storage duration under freezer-based systems. Data collected included fish temperature at hauling, during freezing, and after storage, as well as the handling methods and equipment used by fishermen. The initial body temperature of the fish was 29.3°C at hauling. Fish were sorted by species, size, and quality, then washed and frozen at -18°C for 24 hours. Once frozen, they were packaged and transferred to the fish hold at -13.7°C for storage. The findings highlight the importance of systematic handling, washing, rapid freezing, and controlled storage—to maintain fish quality and extend shelf life.